Osteochondritis Dissecans of the Knee - Conservative Treatment Strategies: A Systematic Review. (July 2019) - Andriolo, Luca; Candrian, Christian; Papio, Tiziana; Cavicchioli, Alessia; Perdisa, Francesco; Filardo, Giuseppe
Objective: Osteochondritis dissecans (OCD) lesions are a relevant problem that affects the long-term prognosis of young patients. The purpose of this study was to analyze the evidence on potential and indications of nonsurgical treatment strategies for knee OCD. Design: The search was conducted on 3 medical electronic databases according to PRISMA guidelines, including reports of any level of evidence dealing with the conservative management of knee OCD. Of 1688 identified records, 55 full-text articles were screened: 27 studies met the inclusion criteria, for a total of 908 knees, and were used for the analysis. Results: No high-level studies were found: 24 articles were case series and 3 case reports, reporting on different treatments summarized in (1) restriction of physical activity, (2) physiokinesitherapy and muscle-strengthening exercises, (3) physical instrumental therapies, (4) limitation of weightbearing, and (5) immobilization. The analysis showed an overall healing rate of 61.4%, with large variability (10.4%-95.8%). A conservative treatment based on restriction of sport and strenuous activities seems a favorable approach, possibly combined with physiokinesitherapy. Negative prognostic factors were also identified: larger lesion size, more severe lesion stages, older age and skeletal maturity, discoid meniscus, and clinical presentation with swelling or locking. Conclusions: The literature on conservative treatments for knee OCD is scarce. Among different non-surgical treatment options, strenuous activity restriction seems a favorable approach, whereas there is no evidence that physical instrumental therapy, immobilization, or weightbearing limitation could be beneficial. However, further studies are needed to improve treatment potential and indications for the conservative management of knee OCD.